Psychometric properties of the European Portuguese version of the Perceived Risk of HIV Scale in the general population and HIV-uninfected partners from sero-different couples - Martins, Alexandra (2019)
Perceived risk of HIV plays an important role in the adoption of protective behaviours and HIV testing. However, few studies have used multiple-item measures to assess this construct. The Perceived Risk of HIV Scale (PRHS) is an 8-item measure that assesses how people think and feel about their risk of HIV infection. This cross-sectional study aimed to assess the psychometric properties (reliability and validity) of the European Portuguese version of the PRHS, including the ability of this scale to discriminate between individuals from the general population and HIV-uninfected partners from sero-different couples on their perceived risk of HIV infection (known-groups validity).